2018
DOI: 10.3389/fmicb.2018.01084
|View full text |Cite
|
Sign up to set email alerts
|

Edwardsiella tarda Sip2: A Serum-Induced Protein That Is Essential to Serum Survival, Acid Resistance, Intracellular Replication, and Host Infection

Abstract: Edwardsiella tarda is a broad-host pathogen that can infect mammals, reptiles, and fish. E. tarda exhibits a remarkable ability to survive in host serum and replicate in host phagocytes, but the underlining mechanism is unclear. In this study, in order to identify E. tarda proteins involved in serum resistance, iTRAQ proteomic analysis was performed to examine the whole-cell protein profiles of TX01, a pathogenic E. tarda isolate, in response to serum treatment. Of the differentially expressed proteins identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 69 publications
0
11
0
1
Order By: Relevance
“…The results showed that the amount of TX01Δ hutZ recovered from the entire (i.e., from the surface and the intracellular milieu) FG cell culture was significantly lower than that of TX01 after infecting for 1 h and 2 h (Figure 9A). It is known that E. piscicida is able to survive and replicate in host cells [29]. To examine whether the hutZ Ep mutation played any role in the intracellular survival of TX01, FG cells were incubated with E. piscicida , and extracellular bacteria were killed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the amount of TX01Δ hutZ recovered from the entire (i.e., from the surface and the intracellular milieu) FG cell culture was significantly lower than that of TX01 after infecting for 1 h and 2 h (Figure 9A). It is known that E. piscicida is able to survive and replicate in host cells [29]. To examine whether the hutZ Ep mutation played any role in the intracellular survival of TX01, FG cells were incubated with E. piscicida , and extracellular bacteria were killed.…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al [28] found that E. piscicida tunes the tricarboxylic acid cycle to evade complement-mediated killing, which reveals a previously unknown membrane potential-dependent mechanism of serum resistance. Two novel serum-induced proteins, Sip1 and Sip2, were found to be essential to serum resistance, which are also different from known mechanisms [29, 51]. Other virulence factors involved in resistance against the bactericidal effect of hos serum include the serine protease autotransporter Tsh, lysozyme inhibitor Ivy, and thioredoxin TrxH [34, 39, 52].…”
Section: Discussionmentioning
confidence: 99%
“…Sip1, also named as Aur or aureolysin, is a seruminduced zinc metalloprotease implicated in serum resistance and is essential for fish infection [95]. In addition, Sip2 (homologue of HypB, a putative hydrogenase) protects E. piscicida in fish serum and significantly increases cellular and tissue infection by allowing the bacteria to cope with acidic stress [96]. Although the direct regulon is unclear, the cyclic AMP receptor protein (CRP) was shown to be essential for flagellar biosynthesis and motility, hemolytic activity, and in vivo virulence in E. piscicida [97].…”
Section: Other Virulence Factors or Determinants And Mechanismsmentioning
confidence: 99%
“…In this study, we also examined the effect of trxH Ep on E. piscicida pathogenicity. It is known that biofilm formation and serum resistance are important parts of the virulence in multiple pathogens such as E. piscicida [17, 35] and H. pylori [48, 49]. In the latter, the inability to acquire iron from serum has been suggested to block H. pylori virulence by weakening its growth and survival in the serum [48].…”
Section: Discussionmentioning
confidence: 99%
“…Cheng et al reported that this bacteria uses the tricarboxylic acid cycle to evade complement-mediated killing [16]. Another study showed that Sip2 in E. piscicida contributes to serum survival, acid resistance, intracellular replication, and host infection [17]. However, studies on the tolerance of E. piscicida to oxidative stress are limited.…”
Section: Introductionmentioning
confidence: 99%